The features of cognitive impairments in patients with type 2 diabetes mellitus and comorbid post covid disorders - Kohut Aнна; Bobryk Марина; Komisarenko Юлія; Khaustova Олена; Chaban Олег (Psychosomatic Medicine and General Practice, 2021)
Background: the consequences of the SARS-CoV-2 pandemic still remain the significant problem for the health care system in the world. In addition, the long-term consequences have been insufficiently studied and predicted for central nervous system in post covid period. The cognitive impairments and affective disorders have been one of the main components of post covid syndrome. It is important for studying especially which cognitive domains could be effected and in which cases in different groups of patients with chronic deseases. These aspects have not been studied well in patients with type 2 diabetes mellitus (DM 2) as the risk group for long-term post covid complications. Aim: the revealing of the affection of probable cognitive domains due to the long-term postcovid effects in DM 2. Results: by the review of studies, the cognitive impairments of such functions: memory, attention, executive functions and language - detected in patients of post covid period. In DM 2 it can correlate with the affection of such domains - operational thinking, attention, memory and executive functions. Conclusions: therefore, it is so important in terms of medication compliance and adherence to treatment, as a result - the negative impact on DM 2 treatment efficiency and quality of life level.